PENGARUH KEPEMILIKAN MANAJEMEN, KEPEMILIKAN DEWAN KOMISARIS, DAN STRATEGI PEMASARAN TERHADAP PROFITABILITAS BANK ( Perbandingan Bank Devisa dan Bank Non Devisa di Indonesia Tahun 2008-2011) - Agriaty Vitha Sandabunga; Anis Chariri (Diponegoro Journal of Accounting, 2013)
The objective of this research is to analyse the influence of Management Ownership, board of commissioner Ownership, Marketing Strategy proxied to the Net Profit Margin (NPM) to profitability (ROA) by Bank Size (SIZE), and total deposits are proxied by the Loan to deposit Ratio (LDR) as a control variable in foreign banks and non banks foreign exchange period 2008-2011. Data used in this study was obtained from the annual report on the whole banks in Indonesia, and Bank reports Publication through the website. The sampling technique used was purposive sampling. The sample in this study 129 foreign banks, 82 non foreign banks and 211 combined foreign and non foreign banks. The analysis technique used is multiple regression to test the hypothesis that the t test and F test.The result shows that the variables and Management Ownership Marketing Strategy proxied to the Net Profit Margin (NPM) has a positive and significant influence toward profitability (ROA) in foreign banks, only Total Deposits proxied to Loan to Deposit Ratio (LDR) has positive and significant influenced toward profitability in non foreign banks, which has a positive effect and significant impact on profitability (ROA), while the combination of the two banks indicates LDR and management Ownership has positive and significant influenced toward profitability (ROA).